TCL1A and ATM are co-expressed in chronic lymphocytic leukemia cells without deletion of 11q - Garding, Angela; Bhattacharya, Nupur; Häbe, Sarah; Müller, Frederike; Weichenhan, Dieter; Idler, Irina; Ickstadt, Katja; Stilgenbauer, Stephan; Mertens, Daniel (Haematologica, the hematology journal, 2013)
Chronic lymphocytic leukemia is characterized by the accumulation of B cells that are resistant to apoptosis. This resistance is induced by pro-survival stimuli from the microenvironment. TCL1 and ATM are central to the pathogenesis of the disease and associated with more aggressive disease. Their protein products have recently been shown to physically interact in leukemic cells and to impact on NF-κB signaling, which is a key regulator of apoptosis. In the present study we show that TCL1 and ATM are significantly co-expressed and up-regulated in malignant cells compared to non-malignant B cells, and that expression of TCL1 is partially deregulated by aberrant DNA-methylation. In addition, complex external stimuli induce essentially similar TCL1 and ATM time-course kinetics. In line with a coordinative regulation of NF-κB signaling by TCL1, its knockdown induced apoptosis in primary leukemia cells. These findings suggest that both genes functionally cooperate to modulate similar apoptosis-related cellular pathways.
Gesehen am 26.02.2021